Improving Vocational High School Students’ Speaking Ability through the One Minute Sharing (OMS) Technique - Retnaningsih, Dewi; Susanti, Ani; Surono, Surono (Journal of Vocational Education Studies, 2025)
Speaking is often perceived as one of the most challenging skills in learning English, including among Grade X Broadcasting students at a vocational high school in Yogyakarta. To address this issue, a Classroom Action Research (CAR) was conducted to investigate the effectiveness of the One Minute Sharing (OMS) technique in enhancing students’ speaking ability. The OMS technique requires students to speak spontaneously for one minute on selected topics, and in this study, it was implemented over two research cycles. Initial observations and a pre-test revealed low speaking proficiency, with an average score of 63 and only 15% of students meeting the Minimum Mastery Criterion (SKM). Furthermore, many students lacked confidence, and only one-third demonstrated strong motivation. In Cycle I, the average speaking score increased to 70, with 63% of students achieving SKM, and motivation levels rising to 60%, although some hesitation persisted. In Cycle II, improvements were made by incorporating more engaging activities, providing direct modelling and feedback, and offering small rewards as appreciation. These refinements resulted in an average score of 80, with 86% of students meeting SKM and an equal percentage reporting greater motivation and confidence in speaking English. The findings indicate that providing regular, individual speaking opportunities through OMS can substantially improve speaking ability, enhance motivation and self-confidence, and foster better classroom engagement. Therefore, the OMS technique can be considered an effective and practical instructional strategy for promoting autonomous speaking practice, particularly in vocational high school contexts.